Study on Influence Characteristics of Natural Gas Leakage in Long-distance Pipelines. Issue 1 (March 2021) - Ding, Cui
Abstract: In order to study the diffusion characteristics of leaking natural gas in long-distance pipeline, natural gas leakage model were established and natural gas diffusion was numerically simulated by fluent. The influences of different airflow velocities and leakage apertures on the concentration distribution of natural gas were analyzed. The research shows that airflow velocity promotes the diffusion of natural gas, and the greater the airflow velocity, the wider the diffusion range and distance of natural gas towards the downwind. The larger the leakage apertures, the larger the concentration and diffusion area of natural gas. Airflow velocities and leakage apertures are the key factors affecting the accumulation of natural gas near the surface. In the case of natural gas leakage in long-distance pipelines, people near the leakage hole should be evacuated to the upwind direction to minimize the risk.